Simultaneous Determination of Furan and Vinyl Acetate in Vapor Phase of Mainstream Cigarette Smoke by GC-MS - XU,AIFEI (2017)
ABSTRACT A simple and sensitive method for simultaneous determination of furan and vinyl acetate (VA) in vapor phase of mainstream cigarette smoke with cold trap and gas chromatography-mass spectrometry (GC-MS) was developed. A Cambridge filter pad (CFP) was placed in front of the impingers of smoking machine to remove the particle phase from cigarette smoke. Furan and VA in vapor phase of mainstream cigarette smoke were collected in two impingers connected in series by filled with methanol at -78°C. The solutions were added with deuterium-labeled furan-d4 and VA-d6 as internal standards and analyzed by GC-MS. The results showed that the calibration curves for furan and VA were linear (r2 > 0.9995) over the studied concentration range. The intra- and inter-day precision values for furan and VA were <7.07% and <9.62%, respectively. The extraction recoveries of furan and VA were in the range of 94.5-97.7% and 92.3-94.9%, respectively. Moreover, the limits of detection for furan and VA were 0.028 µg mL-1 and 1.3 ng mL-1, respectively. The validated method has been successfully applied to determine the emissions of furan and VA in the vapor phase of mainstream cigarette smoke under International Organization for Standardization (ISO) and Canadian Intense (CI) smoking regimen.